STRATEGI PENGEMBANGAN POTENSI DESA MENJADI DESA WISATA DI KABUPATEN TABANAN (Studi Kasus Desa Tegal Linggah, Penebel, Tabanan) - I Wayan Pantiyasa (Jurnal Ilmiah Hospitality Management, 2013)
The purpose of the research is to know the tourism potency of Tegal Linggah village which will be the fondastion to develop the village into community based tourism, the community perception the plan of community based tourism development, and how to make strategic development of community based tourism. The research use the drescriptive statistic analysis and SWOT analysis. The result of the research is to get potencies of Tegal Linggah village, they are natural, culture, social conomic and culinary. Then other potencies are accessibility to the village. The perception of the community to the plan of community based tourism development are 40,75% / very agree, 57,83% / agree, and 1,42 / only still doubt. The strategys in the community based tourism development are: organizing of managemen, making the house rules of th community based tourism, planning of tourist attraction, preparing the infra and supra structure of the community based tourism, socializing to the community, marketing the product of CBT, making the program of cleaning village.Â